Belief-content justification for cases of a priori justification: A neo-Haackian model. Issue 3 (2nd September 2016) - Frank, Neil
Abstract : I differentiate justification of the subject (S-justification) from justification of the content of a belief (C-justification) and note the questions associated with truth conduciveness of justification. I employ Susan Haack's analysis of empirical justification and show how, with certain adaptations, it can account for justification from non-experiential sources, if there are any. I give at least one example from mathematical visual thinking.